High-strength and high-plasticity high-entropy alloy and preparation method thereof

Through the simplified high-entropy alloy preparation method, including ball milling of mixed powders and ultrasonic electromagnetic stirring, the process complexity and cost problems of high-entropy alloys in strength and plasticity optimization are solved, and high-strength and high-plastic high-entropy alloys are realized, with high stability and industrial production potential.

CN120041740APending Publication Date: 2025-05-27JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510280180.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-05-27

AI Technical Summary

Technical Problem

High-entropy alloys face problems such as process complexity, high cost and poor stability in improving strength and plasticity, which limits their application in aerospace, nuclear industry and high-temperature structural materials.

Method used

A simplified preparation method is adopted, including mixing Nb powder and B powder under room temperature and argon protection conditions, followed by ball milling with Ni powder, etc., forming a gradient-distributed mixed powder, and finally melting in the high-entropy alloy melt and ultrasonic electromagnetic stirring is used to obtain a high-strength plastic high-entropy alloy containing nanoparticles.

Benefits of technology

High-entropy alloys with high strength (≥750MPa) and high plasticity (maximum tensile strength ≥1506MPa, fracture strain ≥15.9%) are achieved, reducing process complexity and cost, while improving material stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120041740A_ABST
    Figure CN120041740A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength and high-plasticity high-entropy alloy and a preparation method thereof. The preparation method of the high-strength and high-plasticity high-entropy alloy comprises the steps that firstly, Nb powder and B powder are subjected to long-time ball-milling mixing under argon protection, then the Nb powder and the B powder are mixed with Ni powder according to different proportions, and balls containing gradient mixed powder are sequentially packaged; then, the spheres containing the gradient mixed powder are put into a high-entropy alloy melt, heat preservation is conducted at the temperature of 1600-1800 DEG C, ultrasonic electromagnetic stirring is assisted, and the spheres are completely melted to form the high-entropy alloy melt containing nano-particles. And finally, casting and heat treatment are conducted on the molten liquid under argon gas protection, the high-strength plasticity high-entropy alloy is obtained, and compared with commercial high-entropy alloy, the yield strength of the high-strength plasticity high-entropy alloy obtained through the method is improved by 19.0% or above, the maximum tensile strength is larger than or equal to 20.9%, and the fracture strain is larger than or equal to 26.2%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high entropy alloy preparation, and relates to a high-strength plastic high entropy alloy and a preparation method thereof. Background Art

[0002] High entropy alloys exhibit excellent comprehensive properties due to their composition and structural characteristics. However, in terms of mechanical property optimization, high entropy alloys still face the problem of balancing strength and plasticity, that is, increasing strength often leads to a decrease in plasticity, while enhancing plasticity may sacrifice strength, limiting their application in aerospace, nuclear industry and high-temperature structural materials. In the process of optimizing the strength and plasticity of high entropy alloys, the commonly used methods currently include alloy element optimization, repeated heat treatment and directional solidification, but there are process complexity and difficulty in industrial production. The development cycle of alloy element optimization is long and the cost is high. Improving performance by adjusting the alloy composition requires a large number of experiments and theoretical calculations, resulting in a long R&D cycle and high cost. The interaction between different elements may produce brittle phases or uneven structures, making the material performance unstable; in addition, some key alloy elements are scarce and difficult to obtain, which increases the cost of raw material procurement and brings supply chain risks. Repeated heat treatment usually includes multi-step annealing, quenching, aging, etc., which requires precise control of temperature, time and cooling rate. Its tolerance range is very small, and any slight deviation may affect the final microstructure and mechanical properties. In addition, repeated heat treatment consumes a lot of energy, which significantly increases production costs. The method of directional solidification is highly dependent on professional equipment, which is difficult to operate and has high equipment investment costs. During the solidification process, the cooling rate and temperature gradient need to be controlled with extremely high precision. It is difficult to ensure the consistency of the organization of each batch during mass production; and the existing directional solidification equipment limits the geometry and size of the casting, resulting in workpiece design constraints, which makes it difficult to meet the manufacturing requirements of complex structures. In summary, high-entropy alloys currently still face many process challenges in improving strength and plasticity at the same time. How to reduce costs, simplify the preparation process and improve process stability are technical problems that need to be solved urgently for the industrial application of high-entropy alloys. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a high-strength and high-plasticity high-entropy alloy, and its preparation method comprises the following steps:

[0004] Step 1: at room temperature and under argon protection, Nb powder and B powder are placed in a ball mill at a rotation speed of 40-60 rpm and mixed for 22-26 hours to obtain a mixed powder 1, in which the mass proportion of niobium powder is 75-85% and the mass proportion of boron powder is 15-25%;

[0005] The particle size of the Nb powder is 15-53 microns, and the particle size of the B powder is 5-20 microns;

[0006] Step 2: Under the protection of argon gas, mix the mixed powder 1 obtained in Step 1 with Ni powder at mass ratios of 90 - 93%:8 - 10%, 48 - 53%:48 - 53%, and 9 - 11%:88 - 92% respectively. Use a ball mill to mix them at a rotation speed of 20 - 30 rpm for 3 - 6 hours to obtain mixed powder 2, mixed powder 3, and mixed powder 4;

[0007] The particle size of the Ni powder is 53 - 150 microns;

[0008] Step 3: Package the mixed powder 2 obtained in Step 2 in a nickel spherical shell to obtain sphere 1;

[0009] The mass ratio of the nickel spherical shell to the mixed powder 2 is 45 - 55%:45 - 55%;

[0010] Step 4: Mix sphere 1 in Step 3 with the mixed powder 3 in Step 2 at a mass ratio of 44 - 48%:52 - 56% to obtain mixture A. Then package mixture A in a nickel spherical shell to obtain sphere 2;

[0011] The mass ratio of the nickel spherical shell to mixture A is 45 - 50%:50 - 53%;

[0012] Step 5: Mix sphere 2 in Step 4 with the mixed powder 4 in Step 2 at a mass ratio of 40 - 45%:55% - 60% to obtain mixture B. Then package mixture B in a nickel spherical shell to obtain a sphere containing gradient mixed powder;

[0013] The mass ratio of the nickel spherical shell to mixture B is 53 - 57%:40 - 50%;

[0014] Step 6: Put the sphere containing gradient mixed powder in Step 5 into a high - entropy alloy melt until the sphere containing gradient mixed powder is completely melted in the high - entropy alloy melt. At the same time, use ultrasonic electromagnetic stirring and keep it at 1600 - 1800 °C for 3 - 5 hours to obtain a high - entropy alloy melt containing nanoparticles;

[0015] By mass percentage, the composition of the high - entropy alloy melt is: Ni: 45 - 50%, Cr: 18 - 22%, Co: 20 - 24%, Al: 8 - 10%;

[0016] The mass proportion of the sphere containing gradient mixed powder in the high - entropy alloy melt is 1 wt.% - 3 wt.%;

[0017] Step 7: Cast the high-entropy alloy melt containing nanoparticles obtained in Step 6 under argon protection, and then hold it at 600 - 850 °C for 8 - 10 h to obtain a high-strength and high-plasticity high-entropy alloy with a yield strength ≥ 750 MPa, a maximum tensile strength ≥ 1506 MPa, and a fracture strain ≥ 15.9%.

[0018] Further, the particle size of the Nb powder in Step 1 is 20 - 45 microns, and the particle size of the B powder is 10 - 15 microns.

[0019] Further, the particle size of the Ni powder in Step 2 is 80 - 120 microns. Description of the Drawings

[0020] Figure 1 Perspective schematic diagram of the gradient-distributed mixed powder sphere prepared in Example 1 of the present invention;

[0021] Figure 2 Room-temperature engineering stress-strain curve of the high-strength and high-plasticity high-entropy alloy 1 prepared in Example 2 of the present invention;

[0022] Figure 3 Room-temperature engineering stress-strain curve of the high-strength and high-plasticity high-entropy alloy 2 prepared in Example 3 of the present invention;

[0023] Figure 4 Room-temperature engineering stress-strain curve of the high-strength and high-plasticity high-entropy alloy 3 prepared in Example 4 of the present invention;

[0024] Figure 5 Room-temperature engineering stress-strain curve of the high-entropy alloy 4 in Comparative Example 1 of the present invention. Detailed Embodiments

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0026] Example 1

[0027] A sphere containing gradient-distributed mixed powder, and its preparation method includes the following steps:

[0028] Step 1: Under room temperature and argon protection, put the Nb powder and B powder in a ball mill with a rotation speed of 50 rpm and mix for 24 hours to obtain mixed powder 1. In the mixed powder 1, the mass ratio of niobium powder is 80%, and the mass ratio of boron powder is 20%;

[0029] The particle size of the Nb powder is 30 microns, and the particle size of the B powder is 15 microns;

[0030] Step 2: Under the condition of argon protection, mix the mixed powder 1 obtained in Step 1 with Ni powder at mass ratios of 91%:9%, 50%:50%, and 9%:91% respectively, and ball-mill them at a rotation speed of 25 rpm for 5 hours to obtain mixed powder 2, mixed powder 3, and mixed powder 4;

[0031] The particle size of the Ni powder is 100 microns;

[0032] Step 3: Encapsulate the mixed powder 2 obtained in Step 2 in a nickel spherical shell to obtain sphere 1;

[0033] The mass ratio of the nickel spherical shell to the mixed powder 2 is 50%:50%;

[0034] Step 4: Mix sphere 1 in Step 3 with the mixed powder 3 in Step 2 at a mass ratio of 47%:53% to obtain mixture A, and then encapsulate mixture A in a nickel spherical shell to obtain sphere 2;

[0035] The mass ratio of the nickel spherical shell to mixture A is 48%:52%;

[0036] Step 5: Mix sphere 2 in Step 4 with the mixed powder 4 in Step 2 at a mass ratio of 43%:57% to obtain mixture B, and then encapsulate mixture B in a nickel spherical shell to obtain a sphere containing a gradient mixed powder;

[0037] The mass ratio of the nickel spherical shell to mixture B is 55%:45%;

[0038] Example 2

[0039] High-strength and high-plasticity high-entropy alloy 1, and its preparation method includes the following steps:

[0040] Step 1: Put the sphere containing the gradient mixed powder in Example 1 into the high-entropy alloy melt 1 until the sphere containing the gradient mixed powder is completely melted in the high-entropy alloy melt 1, keep it at 1700 °C for 4 hours, and at the same time use ultrasonic electromagnetic stirring to obtain a high-entropy alloy melt A containing nanoparticles;

[0041] The elemental mass percentage of the high-entropy alloy melt 1 is Ni: 49%, Cr: 20%, Co: 22%, Al: 9%;

[0042] The mass proportion of the sphere containing the gradient mixed powder in the high-entropy alloy melt A is 1 wt.%;

[0043] Step 2: Cast the high-entropy alloy melt A containing nanoparticles obtained in Step 1 under the condition of argon protection, and then keep it at 750 °C for 9 h to obtain high-strength and high-plasticity high-entropy alloy 1;

[0044] In this embodiment, the room-temperature engineering stress-strain curve of the high-strength and high-ductility high-entropy alloy 1 is as follows Figure 2 shown. The yield strength is 750 MPa, the maximum tensile strength is 1549 MPa, and the fracture strain is 17.3%. The test data are shown in Table 1; the structure of the high-strength and high-ductility high-entropy alloy 1 contains uniformly dispersed nano-particles, where the particle size of the nano-particles is 65 - 80 nanometers. The above-mentioned nano-particles and the high-entropy alloy matrix achieve an effective synergistic effect, simultaneously improving the strength and ductility of the high-entropy alloy.

[0045] Example 3

[0046] The high-strength and high-ductility high-entropy alloy 2, and its preparation method includes the following steps:

[0047] Step 1: Put the sphere containing the gradient mixed powder in Example 1 into the high-entropy alloy melt 2 until the sphere containing the gradient mixed powder is completely melted in the high-entropy alloy melt 2. Keep it at 1600 °C for 6 hours, and at the same time use ultrasonic electromagnetic stirring to obtain the high-entropy alloy melt B containing nano-particles;

[0048] The elemental mass percentage of the high-entropy alloy melt 2 is: Ni: 50%, Cr: 21%, Co: 21%, Al: 8%;

[0049] The mass ratio of the sphere containing the gradient mixed powder in the high-entropy alloy melt B is 2 wt.%;

[0050] Step 2: Cast the high-entropy alloy melt B containing nano-particles obtained in Step 1 under argon protection, and then keep it at 850 °C for 8 h to obtain the high-strength and high-ductility high-entropy alloy 2;

[0051] In this embodiment, the room-temperature engineering stress-strain curve of the high-strength and high-ductility high-entropy alloy 2 is as follows Figure 3 shown. The yield strength is 784 MPa, the maximum tensile strength is 1506 MPa, and the fracture strain is 16.8%. The test data are shown in Table 1; the structure of the high-strength and high-ductility high-entropy alloy 2 contains uniformly dispersed nano-particles, where the particle size of the nano-particles is 70 - 85 nanometers. The above-mentioned nano-particles and the high-entropy alloy matrix achieve an effective synergistic effect, simultaneously improving the strength and ductility of the high-entropy alloy.

[0052] Example 4

[0053] The high-strength and high-ductility high-entropy alloy 3, and its preparation method includes the following steps:

[0054] Step 1: Place the sphere containing the gradient mixed powder in Example 1 into the high-entropy alloy melt 3 until the sphere containing the gradient mixed powder is completely melted in the high-entropy alloy melt 3. Keep it at 1800 °C for 5 hours while using ultrasonic electromagnetic stirring, and then obtain the high-entropy alloy melt C containing nanoparticles;

[0055] The elemental mass percentages of the high-entropy alloy melt 3 are: Ni: 47%, Cr: 21%, Co: 22%, Al: 10%;

[0056] The mass proportion of the sphere containing the gradient mixed powder in the high-entropy alloy melt C is 3 wt.%;

[0057] Step 2: Cast the high-entropy alloy melt C containing nanoparticles obtained in Step 1 under argon protection, and then keep it at 850 °C for 8 h to obtain the high-strength and high-plasticity high-entropy alloy 3;

[0058] The room-temperature engineering stress-strain curve of the high-strength and high-plasticity high-entropy alloy 3 prepared in this example is as Figure 4 shown. The yield strength is 812 MPa, the maximum tensile strength is 1573 MPa, and the fracture strain is 15.9%. The test data are shown in Table 1; The high-strength and high-plasticity high-entropy alloy 3 structure contains uniformly dispersed nanoparticles, where the particle size of the nanoparticles is 75 - 95 nanometers. The above-mentioned nanoparticles and the high-entropy alloy matrix achieve an effective synergistic effect, simultaneously improving the strength and plasticity of the high-entropy alloy.

[0059] Comparative Example 1

[0060] High-entropy alloy 4, its preparation method includes the following steps:

[0061] Step 1: Keep the high-entropy alloy melt 4 at 1700 °C for 4 hours while using ultrasonic electromagnetic stirring;

[0062] The elemental mass percentages of the high-entropy alloy melt 4 are: Ni: 49%, Cr: 20%, Co: 22%, Al: 9%;

[0063] Step 2: Cast the high-entropy alloy melt 4 obtained in Step 1 under argon protection, and then keep it at 750 °C for 9 hours to obtain the high-entropy alloy 4;

[0064] The room-temperature engineering stress-strain curve of the high-entropy alloy 4 prepared in Comparative Example 1 is as Figure 5 shown. The yield strength is 630 MPa, the tensile strength is 1183 MPa, and the fracture strain is 12.6%. The test data are shown in Table 1.

[0065] The difference between Examples 2 - 4 of the present invention and Comparative Example 1 lies in:

[0066] In Example 2, the yield strength and tensile strength of the high-strength and high-ductility high-entropy alloy 1 increased by 19.0% and 20.9% respectively compared with Comparative Example 1, and the fracture strain increased by 37.3%. Therefore, the mechanical properties in this example are better than those in Comparative Example 1.

[0067] In Example 3, the yield strength and tensile strength of the high-strength and high-ductility high-entropy alloy 2 increased by 24.4% and 27.3% respectively compared with Comparative Example 1, and the fracture strain increased by 33.3%. Therefore, the mechanical properties in this example are better than those in Comparative Example 1.

[0068] In Example 4, the yield strength and tensile strength of the high-strength and high-ductility high-entropy alloy 3 increased by 28.9% and 33.0% respectively compared with Comparative Example 1, and the fracture strain increased by 26.2%. Therefore, the mechanical properties in this example are better than those in Comparative Example 1.

[0069] Comparative Example 2

[0070] In the article "Formation of lamellar eutectic structure and improved mechanical properties of directionally solidified Al0.9CoCrNi2.1 high-entropy alloy" published by Xu et al. in Volume 173 of Intermetallics in 2018, under a high-purity argon atmosphere, an ingot with a nominal composition of Al0.9CoCrNi2.1 (at.%) was synthesized by the method of vacuum levitation melting, and remelted more than five times to improve its chemical homogeneity. The mass percentages of each element are: Al: 9.4%, Co: 22.8%, Cr: 20.1%, Ni: 47.7%. Subsequently, by the method of directional solidification, high-entropy alloys were prepared at truncation rates of 6, 15, 30, 60, and 120 μm / s respectively. Among the high-entropy alloys prepared, the maximum yield strength obtained at a truncation rate of 15 μm / s was 674 MPa, and the maximum tensile strength and fracture strain obtained at a truncation rate of 120 μm / s were the best, being 1304 MPa and 13.4% respectively.

[0071] Compared with Comparative Example 2, the present invention avoids the complex process and operation cost of directional solidification, and simultaneously strengthens the strength and plasticity of the high-entropy alloy. The yield strength, maximum tensile strength, and fracture strain in Examples 2-4 of the present invention are all better than those in Comparative Example 2, indicating that a high-strength and high-ductility high-entropy alloy can be prepared by the present invention, and the strength and plasticity are simultaneously improved compared with the prior art.

[0072] In Examples 2-4 of the present invention, the components, ratios, and process parameters used are all different. Among them, the yield strength and maximum tensile strength of the high-strength and high-plasticity high-entropy alloy 3 obtained in Example 4 are the highest, and the fracture strain of the high-strength and high-plasticity high-entropy alloy 1 in Example 2 is the largest. In addition, the effects obtained in all examples are significantly better than those achieved by the prior art. This shows that the excellent effects obtained by the present invention are not determined by a certain component, ratio, process, or process parameter, but are achieved through the synergistic regulation of the interaction between components, component ratios, processes, and process parameters. And only within the scope of protection of the claims of the present invention can the most significant technical effects be achieved. At the same time, the present invention has a more uniformly arranged eutectic lamellar structure. At the same time, the matrix of the high-strength and high-plasticity high-entropy alloy prepared by the present invention also contains uniformly distributed nanoparticles with a particle size of 60-100 nanometers. These microstructures, through the synergistic regulation with the matrix, preferably support the simultaneous improvement of the strength and plasticity of the high-entropy alloy.

[0073] Table 1 Comparison of the mechanical properties of the high-entropy alloys in the comparative example and each example

[0074]

[0075] In summary: Compared with the prior art, the present invention omits complex processes such as the addition of precious metal elements and directional solidification. The obtained alloy simultaneously improves the strength and plasticity, not only reducing the raw material addition cost, but also simplifying the process, having low operating costs, and being easy to realize large-scale industrial production. In addition, due to the synergistic regulation of components, ratios, and process parameters involved in the method, it has high flexibility. In the future, different performance products can be further optimized and customized according to specific requirements, showing broad market prospects and scientific research value, thus promoting the wide application and industrial production of high-performance high-entropy alloys in the fields of aviation, energy, and other high-end equipment.

Claims

1. High-strength and high-plasticity high-entropy alloy, characterized in that: Its preparation method comprises the following steps: Step 1: at room temperature and under argon protection, Nb powder and B powder are placed in a ball mill at a rotation speed of 40-60 rpm and mixed for 22-26 hours to obtain a mixed powder 1, in which the mass proportion of niobium powder is 75-85% and the mass proportion of boron powder is 15-25%; The particle size of the Nb powder is 15-53 microns, and the particle size of the B powder is 5-20 microns; Step 2, under argon protection, the mixed powder 1 obtained in step 1 and Ni powder were mixed in a ball mill at a speed of 20-30 rpm for 3-6 hours in a mass ratio of 90-93%:8-10%, 48-53%:48-53%, and 9-11%:88-92% to obtain mixed powder 2, mixed powder 3, and mixed powder 4; The Ni powder particle size is 53-150 microns; Step 3: encapsulate the mixed powder 2 obtained in step 2 in a nickel spherical shell to obtain a sphere 1; The mass ratio of the nickel spherical shell to the mixed powder 2 is 45-55%:45-55%; Step 4: Mix the sphere 1 in step 3 with the mixed powder 3 in step 2 at a mass ratio of 44-48%:52-56% to obtain a mixture A, and then encapsulate the mixture A in a nickel spherical shell to obtain a sphere 2; The mass ratio of the nickel spherical shell to the mixture A is 45-50%:50-53%; Step 5: Mix the sphere 2 in step 4 with the mixed powder 4 in step 2 at a mass ratio of 40-45%:55%-60% to obtain a mixture B, and then encapsulate the mixture B in a nickel spherical shell to obtain a sphere containing a gradient mixed powder; The mass ratio of the nickel spherical shell to the mixture B is 53-57%:40-50%; Step 6: Place the sphere containing the gradient mixed powder in step 5 into a high entropy alloy melt until the sphere containing the gradient mixed powder is completely dissolved in the high entropy alloy melt, and simultaneously use ultrasonic electromagnetic stirring to keep the temperature at 1600-1800° C. for 3-5 hours to obtain a high entropy alloy melt containing nanoparticles; According to mass percentage, the composition of the high entropy alloy melt is: Ni: 45-50%, Cr: 18-22%, Co: 20-24%, Al: 8-10%; The mass proportion of the spheres containing the gradient mixed powder in the high entropy alloy melt is 1wt.%-3wt.%; Step 7: Cast the high-entropy alloy melt containing nanoparticles in step 6 under argon protection conditions, and then keep it at 600-850° C. for 8-10 hours to obtain a high-strength and plastic high-entropy alloy with a yield strength of ≥750MPa, a maximum tensile strength of ≥1506MPa, and a fracture strain of ≥15.9%.

2. The high-strength ductile high-entropy alloy according to claim 1, characterized in that: The particle size of the Nb powder in step 1 is 20-45 microns, and the particle size of the B powder is 10-15 microns.

3. The high-strength ductile high-entropy alloy according to claim 1, characterized in that: The Ni powder particle size in step 2 is 80-120 microns.